RADIOTHERAPY SERVICES IN CANCER MANAGEMENT AT THE LAGOS UNIVERSITY TEACHING HOSPITAL, IDI-ARABA; PATIENTS PERSPECTIVE - Sowunmi AC; Ibitoye AZ; Alabi AO; Fatiregun OA (Ntec Specialist, 2015)
Background: Cancer is a group of diseases characterized by uncontrolled growth and spread of abnormal cells. The incidence of cancer is on the increase, due to growth and ageing of the global population. More than half of all cancers (56.8%) and cancer deaths (64.9%) in 2012 occurred in less developed regions of the world, and these proportions will increase. The treatment of cancer has undergone evolutionary changes as understanding of the underlying biological processes has increased. It is estimated that 52% of cancer patients need the service of Radiotherapy at least once at one time or the other during the course of their disease. Objective: To determine the knowledge of Radiotherapy as a treatment modality in Cancer Management and to assess the perception to Radiotherapy services among patients receiving treatment at the Radiotherapy department of the Lagos University Teaching Hospital Idi-araba. Method: Data collection was by semi structured questionnaires filled by all patients undergoing radiotherapy in the Radiotherapy department of Lagos University Teaching Hospital over a period of two months. A total of 93 questionnaires were reviewed. Data obtained were collated and analyzed using SPSS statistics [Social Sciences Statistical Package] 17.0 version. Results: Majority, Fifty six (60.2%) of the respondents were from the age group of 41-65. Seventy-four(79.6%) respondents had not heard of radiotherapy before they started treatment. Sixty-one (65.6%) of the respondents said they were properly informed about radiotherapy before they started the treatment. Seventy-two (77.4%) respondents think radiotherapy is effective and 90(96.8%) respondents said radiotherapy is too expensive. Majority, Forty eight (51.6%) said the waiting time before they receive treatment is too long.